2012
DOI: 10.4049/jimmunol.1200409
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Cerebrovascular Transmigration Triggers Rapid Neurotoxicity through Release of Proteases Associated with Decondensed DNA

Abstract: Cerebrovascular inflammation contributes to diverse central nervous system (CNS) disorders through mechanisms that are incompletely understood. The recruitment of neutrophils to the brain can contribute to neurotoxicity, particularly during acute brain injuries such as cerebral ischaemia, trauma and seizures. However, the regulatory and effector mechanisms that underlie neutrophil-mediated neurotoxicity are poorly understood. Here we show that mouse neutrophils are not inherently toxic to neurons but that tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
179
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 188 publications
(187 citation statements)
references
References 53 publications
6
179
1
1
Order By: Relevance
“…The authors postulated that neutrophils promote this phenomenon, thereby facilitating massive leukocyte influx through the compromised BSCB. In support of this hypothesis, in vitro experiments by Allen et al (89) demonstrated that neutrophils acquire a neurotoxic phenotype upon cerebrovascular transendothelial migration, releasing soluble factors and proinflammatory cytokines, which could facilitate such an influx into the CNS. Interestingly, this neurotoxic phenotype of neutrophils was acquired when neutrophils transmigrated across an IL-1-stimulated brain endothelium.…”
Section: Discussionmentioning
confidence: 91%
“…The authors postulated that neutrophils promote this phenomenon, thereby facilitating massive leukocyte influx through the compromised BSCB. In support of this hypothesis, in vitro experiments by Allen et al (89) demonstrated that neutrophils acquire a neurotoxic phenotype upon cerebrovascular transendothelial migration, releasing soluble factors and proinflammatory cytokines, which could facilitate such an influx into the CNS. Interestingly, this neurotoxic phenotype of neutrophils was acquired when neutrophils transmigrated across an IL-1-stimulated brain endothelium.…”
Section: Discussionmentioning
confidence: 91%
“…Aberrant NET formation has been associated with tissue damage, autoimmunity, and cancer development (45)(46)(47)(48). It was recently demonstrated that NETs were involved in transfusionrelated acute lung injury (46), neurotoxicity (47), and thrombosis (48).…”
Section: Discussionmentioning
confidence: 99%
“…It was recently demonstrated that NETs were involved in transfusionrelated acute lung injury (46), neurotoxicity (47), and thrombosis (48). Histones, which are major components of NETs, were furthermore shown to induce epithelial and endothelial cell death (49).…”
Section: Discussionmentioning
confidence: 99%
“…Granulocyte numbers were not increased in infected mice independently of infarct size either. Although after IL-1-mediated cerebrovascular transmigration granulocytes acquire a neurotoxic phenotype, and IL-1 actions can worsen injury in the brain via granulocytes in vivo, 30,39 increased numbers of parenchymal granulocytes in the current experimental model might be indirectly associated with infection status and thus bigger infarcts. Nevertheless, systemic or perivascular granulocyte responses might mediate brain injury independently of the cells in the brain parenchyma, although this was not tested experimentally in the present study.…”
mentioning
confidence: 84%